Enhanced Sensitivity to Ethanol-Induced Inhibition of LTP in CA1 Pyramidal Neurons of Socially Isolated C57BL/6J Mice: Role of Neurosteroids - Talani, Giuseppe; Biggio, Giovanni; Sanna, Enrico (Frontiers in Endocrinology, 2011)
Ethanol (EtOH)–induced impairment of long-term potentiation (LTP) in the rat hippocampus is prevented by the 5α-reductase inhibitor finasteride, suggesting that this effect of EtOH is dependent on the increased local release of neurosteroids such as 3α,5α-THP that promote GABA–mediated transmission. Given that social isolation (SI) in rodents is associated with altered plasma and brain levels of such neurosteroids as well as with an enhanced neurosteroidogenic action of EtOH, we examined whether the inhibitory effect of EtOH on LTP at CA3-CA1 hippocampal excitatory synapses is altered in C57BL/6J mice subjected to SI for 6 weeks in comparison with group-housed (GH) animals. Extracellular recording of fEPSPs as well as patch-clamp analysis were performed in hippocampal slices prepared from both SI and GH mice. Consistent with previous observations, recording of fEPSPs revealed that the extent of LTP induced in the CA1 region of SI mice was significantly reduced compared with that in GH animals. EtOH (40 mM) inhibited LTP in slices from SI mice but not in those from GH mice, and this effect of EtOH was abolished by co-application of 1 µM finasteride. Current-clamp analysis of CA1 pyramidal neurons revealed a decrease in action potential frequency and an increase in the intensity of injected current required to evoke the first action potential in SI mice compared with GH mice, indicative of a decrease in neuronal excitability associated with SI. Together, our data suggest that SI results in reduced levels of neuronal excitability and synaptic plasticity in the hippocampus. Furthermore, the increased sensitivity to the neurosteroidogenic effect of EtOH associated with SI likely accounts for the greater inhibitory effect of EtOH on LTP in SI mice. The increase in EtOH sensitivity induced by SI may be important for the changes in the effects of EtOH on anxiety and on learning and memory associated with the prolonged stress attributable to social isolation.